2022
DOI: 10.1177/18632521221126926
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for treatment decisions in distal radial physeal injuries: A multicenter retrospective study

Abstract: Background: There are no clearly defined guidelines for the management of distal radial physeal injuries. We aimed to identify the risk factors for patients with distal radial physeal trauma for the risk of deformity, physeal closure, and revision procedure and develop a predictive model. Methods: The retrospective study included patients less than 16 years old with displaced distal radial physeal injuries treated between 2011 and 2018 across five centers in the United Kingdom. Deformity was defined as a volar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a recent meta-analysis by Khan et al, the damage to the growth plate that occurs at the time of the injury is the main cause for a premature physeal arrest whereby fracture types SH III, SH IV and SH V represent the most signficant risk factor [16]. Repeated manipulation has been consistently stated as a risk factor for premature physeal arrest, primarily because of studies by Aitken [9], Lee [12] and more recently Kannan et al [17]. Cannata and Lee have reported that malunited fractures did not for premaphyseal arrest in their studies [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis by Khan et al, the damage to the growth plate that occurs at the time of the injury is the main cause for a premature physeal arrest whereby fracture types SH III, SH IV and SH V represent the most signficant risk factor [16]. Repeated manipulation has been consistently stated as a risk factor for premature physeal arrest, primarily because of studies by Aitken [9], Lee [12] and more recently Kannan et al [17]. Cannata and Lee have reported that malunited fractures did not for premaphyseal arrest in their studies [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The age of the patient should also be taken into account. Kannan et al have shown that the odds for distal radius deformity are significantly higher if the child is older than 12,5 years of age [17].…”
Section: Discussionmentioning
confidence: 99%
“…This paper from Newcastle (UK) examines distal radial physeal injuries and attempts to answer this question. 5 Receiver operating characteristic analysis showed that an age over 12.5 years and a sagittal angulation of > 21.7° carried with it a signifirisk of final residual deformity, and that immobilization of less than 4.5 weeks had a higher rate of revision. Nomograms were constructed providing a pragmatic multivariate model, and anatomical reduction is recommended according to the above parameters by the model.…”
Section: A Prediction Model For Treatment Decisions In Distal Radial ...mentioning
confidence: 99%
“…This paper from Newcastle (UK) examines distal radial physeal injuries and attempts to answer this question. 5 Most distal radius physeal fractures occur in children over ten years of age, where older children unsurprisingly have more residual deformity given the short time for remodelling, but younger children have higher rates of physeal arrest. Controversy exists regarding optimal management and the degree of apposition and angular deformity which is acceptable.…”
Section: A Prediction Model For Treatment Decisions In Distal Radial ...mentioning
confidence: 99%